Is performance in repeated rowing trials improved after induced blood alkalosis? - Carr, A. J.; Slater, G. J.; Dawson, B.; Gore, C. J.; Burke, L. M. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Oral sodium bicarbonate (NaHCO3) supplementation has been found to enhance rowing performance (3). Acute loading protocols are frequently used and are associated with induced blood alkalosis, marked by increases in blood bicarbonate concentration [HCO3 -] of ~6mmol/L and blood pH increases of ~0.05. A disadvantage of acute oral supplementation is the incidence of gastro-intestinal symptoms (GIS), and it has been suggested that ingesting NaHCO3 over several days prior to the exercise effort or competition (chronic loading) could reduce the severity of such side effects (1), while still inducing similar levels of alkalosis and improved performance (4). This study aimed to compare the effect of acute and chronic NaHCO3 loading on blood alkalosis ([HCO3-] and pH), blood lactate concentration [La-], and gastro-intestinal symptoms, as well as performance in repeated rowing ergometer trials with similar timing to that which occurs during a regatta with heats conducted a few days apart. Methods Seven well-trained rowers (3 females & 4 males; mean±SD age 25.0±11.7y; body mass 79.7±10.8kg; sum of 7 skinfolds 76.3±21.7mm) completed a total of six, 2km ergometer tests. Each participant performed two trials (48h apart) per week over a 3-week period. There were three conditions - Acute NaHCO3 loading (trials A1 & A2), Chronic NaHCO3 loading (trials C1 & C2) and Placebo (trials P1 & P2), and each week the subjects` two trials were completed under the same condition, with the conditions assigned in semi-counterbalanced order. For acute loading, subjects ingested 0.3g/kg BM NaHCO3 in 30 min, commencing 120 min before exercise. The chronic loading (0.1g/kg BM ingested in a standardised protocol 5 times per day with food) commenced 24 h before the first of two ergometer tests, which were performed on days 2 and 4 of the chronic loading period. Capillary blood samples were collected and analysed (iSTAT) at the pre-ingestion, pre-warm up and post-test time points. Gastro-intestinal symptoms were quantified via questionnaire at the same time points. A contemporary statistical approach was used (1) with pair-wise comparisons between the six trials for blood pH, HCO3 - and lactate concentration [La-], performance measures and GIS, with the smallest worthwhile change set at 0.2 SD of the between group Placebo1 trial. Results [HCO3-] The highest mean [HCO3-] of 32.4mmol/L was recorded prior to the warm up in the acute (A1) trial, which was substantially greater than that recorded for the first placebo and chronic loading trials (C1 and P1). pH In both acute loading conditions (A1 and A2), the peak pH was 7.50, which was substantially greater compared with that recorded in both the first and second chronic and placebo trials. [La-] Peak post-exercise blood lactate concentration was observed after the A2 trial (15.9mmol/L), and the blood lactate concentration after the A1 and A2 trials was substantially greater than that following the first and second placebo and chronic loading trials. GIS The two highest post-test ratings for gastro-intestinal symptoms were recorded after chronic and placebo trials (C1 and P1), and these ratings were both substantially greater than after the A1 trial. Performance There were trivial differences in mean power between the chronic, acute and placebo conditions (276±62W, 280±65W, 285±59W respectively). Discussion/Conclusion In these subjects, the acute NaHCO3 loading protocol was most effective at inducing blood alkalosis; it induced the greatest pre-exercise pH and [La-] compared with both chronic NaHCO3 and placebo ingestion, and was also associated with the lowest post-exercise gastro-intestinal symptoms. Despite the greater blood alkalosis, ergometer performances were similar for the acute, chronic and placebo conditions. These results are inconsistent with previous research that has reported chronic loading to be associated with a blood alkalosis similar to acute loading values (4), and improved rowing performance (3). The current investigation suggests that an increased blood alkalosis may not necessarily be associated with improved rowing performances although it could be that the calibre of rowers used was unable to benefit from the blood alkalosis. Alternatively, it could be that despite being asked to present in a similar state for six performances, other factors such as motivation and fatigue from training or the subsequent performance trials confounded their performances to a greater extent than could be attributable to blood alkalosis.